Two-dimensional bright and dark-in-bright dipolar Bose-Einstein condensate solitons on a one-dimensional optical lattice - Adhikari, S. K. [UNESP] (IOP Publishing, 2016)
We study the statics and dynamics of anisotropic, stable, bright and dark-in-bright dipolar quasi-two-dimensional Bose-Einstein condensate (BEC) solitons on a one-dimensional (1D) optical-lattice (OL) potential. These solitons mobile in a plane perpendicular to a 1D OL trap can have both repulsive and attractive contact interactions. Dark-in-bright solitons are the excited states of bright solitons. The solitons, when subjected to a small perturbation, exhibit sustained breathing oscillation. Dark-in-bright solitons can be created by phase imprinting a bright soliton. At medium velocities the collision between two solitons is found to be quasi-elastic. Results are demonstrated by a numerical simulation of the three-dimensional mean-field Gross-Pitaevskii equation in three spatial dimensions employing realistic interaction parameters for a dipolar 164Dy BEC.
Keywords: optical lattice; two-dimensional soliton